FRET-mediated near infrared whispering gallery modes: studies on the relevance of intracavity energy transfer with Q-factors. (6th December 2017) - Oki, Osamu; Kushida, Soh; Mikosch, Annabel; Hatanaka, Kota; Takeda, Youhei; Minakata, Satoshi; Kuwabara, Junpei; Kanbara, Takaki; Dao, Thang D.; Ishii, Satoshi; Nagao, Tadaaki; Kuehne, Alexander J. C.; et al.
Abstract : NIR WGM resonators are fabricated from energy-donating and accepting conjugated polymers. Abstract : Near infrared (NIR) optical microsphere resonators are prepared by coassembly of energy-donating and accepting conjugated polymers. In the microspheres, fluorescence resonance energy transfer occurs, leading to sharp and periodic photoluminescence from whispering gallery modes in the NIR region with Q -factors as high as 600.